The mathematical and experimental analysis on the steady-state operating temperature of bifacial photovoltaic modules. (August 2020) - Zhang, Zhen; Wu, Minyan; Lu, Yue; Xu, Chuanjia; Wang, Lei; Hu, Yunfei; Zhang, Fei
Abstract: The operating temperature of bifacial photovoltaic (PV) module affects its power generation and reliability. Combined with view factor model of ground reflectivity on module backside, a thermal steady-state model is established to analyze the thermal performance of bifacial module in this paper. The module operating temperatures under three different installation conditions of roof cement ground, water surface and grassland are calculated and simulated by ANSYS software, and the experiments are designed to analyze and verify it. Based on the difference of reflectivity and heat capacity of different ground for the PV module installation, the effects of ground type and module material on bifacial module temperature and its mechanism are analyzed quantitatively. According to the simulation and experiment results, the operating temperatures of the bifacial modules installed on the roof cement ground, water surface and grassland are 44.7 °C, 41.5 °C, 43.2 °C respectively, under the setting environment condition with specific irradiance, wind speed and ambient temperature. The temperature difference of 1.7 °C–3.2 °C is caused by ground reflectivity and temperature. The operating temperature difference between glass-glass and glass-backsheet module is less than 0.4 °C under the standard condition. The conductivity and emissivity of encapsulation material does not show strong influence on module operating temperature. Highlights: The thermal models of combined view factor and heat transfer are established. The effects of ground reflectivity, temperature and module material are analyzed. The heat sources of cells and encapsulation layers are calculated by ray tracing. Evaluate the module operating temperatures in different installation conditions.